Proximity and size of protected areas in Asian borderlands enable transboundary conservation - Kamath, Vignesh; Oliveras Menor, Imma; Macdonald, David W.; Farhadinia, Mohammad S. (Frontiers in Conservation Science, 2024)
Asia has over 80% of the Earth’s border hotspots for threatened transboundary wildlife. Yet, only limited research has been done on the distribution of protected areas across international borders in Asia. Spatial analysis of protected areas across 42 Asian countries was carried out to understand the distribution, proximity and land-use change in two cases of protected areas across different buffer distances from the borders. Our study demonstrated that Asian countries have larger areas protected near country borders, particularly up to 50 km from borders, as compared to regions further away from the border. Importantly, the median distance between protected areas across international borders is almost three times shorter compared to the median distance between protected areas within the country. Therefore, Asian borderlands provide opportunities for increasing connectivity across the borders. However, the rate of change in natural habitats within protected areas was not related to their distance from the border. Larger extent of multi-use protected areas (IUCN1-6+) near borders compared to strict protected areas (IUCN 1-4) can facilitate the engagement of communities, which are crucial in transboundary conservation initiatives. Our findings can help Asian countries as they work towards their commitments as part of the Kunming-Montreal Global Biodiversity Framework to protect at least 30% of the Earth’s surface area by 2030.